Commitment without Reputation: Renegotiation-Proof Contracts under Asymmetric Information - Emanuele Gerratana; Levent Koçkesen (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
This paper characterizes equilibrium outcomes of extensive form games with incomplete information in which players can sign renegotiable contracts with third-parties. Our aim is to understand the extent to which third-party contracts can be used as commitment devices when it is impossible to commit not to renegotiate them. We characterize renegotiation-proof contracts and strategies for general extensive form games with incomplete information and apply our results to two-stage games. If contracts are observable, then the second mover obtains her best possible payoff given that she plays a renegotiation-proof strategy and the first mover best responds. If contracts are unobservable, then a "folk theorem" type result holds: Any outcome in which the second mover best responds to the first mover's action on the equilibrium path and the first mover receives at least his "individually rational payoff", can be supported. We also apply our results to games with monotone externalities and to a model of credibility of monetary policy and show that in both cases renegotiation-proofness imposes a very simple restriction.
Keywords: C72; D80; L13; 330; Third-Party Contracts; Commitment; Strategic Delegation; Renegotiation; Asymmetric Information; Renegotiation-Proofness; Entry-Deterrence; Monetary Policy